2010
DOI: 10.1021/nn102112b
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Techniques for Assessing and Controlling the Dispersion and Biological Effects of Multiwalled Carbon Nanotubes in Mammalian Tissue Culture Cells

Abstract: In vivo studies have demonstrated that the state of dispersion of carbon nanotubes (CNT) plays an important role in generating adverse pulmonary effects. However, little has been done to develop reproducible and quantifiable dispersion techniques to conduct mechanistic studies in vitro. This study was to evaluate the dispersion of multi-walled carbon nanotubes (MWCNT) in tissue culture media, with particular emphasis on understanding the forces that govern agglomeration and how to modify these forces. Quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
218
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(228 citation statements)
references
References 49 publications
7
218
0
Order By: Relevance
“…[40][41][42] Aspiration of a welldispersed SWCNT preparation also caused more transient inflammation and persistent interstitial fibrosis than poorly dispersed SWCNTs. 15 In contrast, poorly dispersed SWCNTs caused a greater granulomatous response.…”
Section: B Agglomerates Versus Dispersed Structuresmentioning
confidence: 99%
“…[40][41][42] Aspiration of a welldispersed SWCNT preparation also caused more transient inflammation and persistent interstitial fibrosis than poorly dispersed SWCNTs. 15 In contrast, poorly dispersed SWCNTs caused a greater granulomatous response.…”
Section: B Agglomerates Versus Dispersed Structuresmentioning
confidence: 99%
“…CNTbased multimodality imaging and therapy have been proposed for a variety of medical applications, such as carriers for chemotherapeutic drugs (17, 18), Raman detection and imaging (19,20), photoacoustic imaging, and photothermal therapy of cancers (6, 21). Meanwhile, of equal importance there is the emerging field of nanotoxicology, which aims to address the biosafety of these engineered nanoparticles, in particular, how these nanoparticles interact with human proteins in vivo (22)(23)(24)(25).Many studies have been performed on the biological effects of carbon nanotubes, and the interactions between proteins and CNTs (nanoparticle-protein corona) are believed to play an important role in the biological effects of CNTs (26-28). For example, CNTs could bind with pulmonary surfactant proteins A and D and then lead to susceptibility of lung infection and emphysema in mice (29).…”
mentioning
confidence: 99%
“…CNTbased multimodality imaging and therapy have been proposed for a variety of medical applications, such as carriers for chemotherapeutic drugs (17, 18), Raman detection and imaging (19,20), photoacoustic imaging, and photothermal therapy of cancers (6, 21). Meanwhile, of equal importance there is the emerging field of nanotoxicology, which aims to address the biosafety of these engineered nanoparticles, in particular, how these nanoparticles interact with human proteins in vivo (22)(23)(24)(25).…”
mentioning
confidence: 99%
“…CNTs have been shown to induce toxicity via a few mechanisms, one of which requires adsorption of a cell to the CNT and subsequent mechanical piercing of the cell by the CNT (Kang et al, 2007). Wang et al (2010) showed that degree of dispersability influences toxicity and may be mediated by improving the interaction of the CNT with cell membranes or by increased bioavailability. The ability of dye-CNT complexes to induce toxicity to microbes was shown to be mediated by the photoactivated production of ROS (Banerjee et al, 2010).…”
mentioning
confidence: 99%